PENDIDIKAN DALAM MASYARAKAT MODERN SEDERHANA - Mesrawati Simbolon (Ensiklopedia Education Review, 2020)
One very basic difference between education in a simple society and modern society is a shift from the need for individuals to learn something that is agreed upon by everyone for their survival, both present and future. The greater the knowledge and complex skills to be learned, the longer it will take for the continuity of social life. The task of education in society is to arouse intellectual curiosity, that is, attention to knowledge that is separate from its practical application. This is not easy, because it requires attitude, discipline and intellect that is not pragmatic, instant and fast-paced. With the existence of educational comparisons in this society, a more balanced, critical comparison of our education system is processed. It is clear, that in education there is no bias in moving complex practices into a culture that is more complex and large and expecting results. On the other hand, the success of a simple society in taking care of certain aspects in encouraging their education will encourage us to overcome our educational problems such as the problem of integrating children into the community into their environment and arousing student interest, motivation and attention during the education period. It is necessary to look for solutions with a greater perspective and optimism. Keywords: Education, Society, Modern, Simple.